Knowledge and Practices of The Gandu Village, Sleman Community Againts Covid-19 - Capritasari, Rafiastiana; Arifiyah, Adilla (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Background: The Covid-19 pandemic caused by infection with the CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) virus has become an event that threatens public health throughout the world. The disease caused by the corona virus is a new type of disease that was discovered in 2019 and has never been identified to infect humans before. Methods: quantitative research with a cross sectional design. The sample in this study was 180 respondents selected by purposive sampling technique. Knowledge and behavior data from respondents were collected through online and offline questionnaires distributed from August to October 2021. Data analysis used bivariate analysis. Results : the results showed that the majority of people showed good levels of knowledge about the pandemic Covid-19 (87,7%) and good practices (77,2%). Statistic results have shown p=0,000 meaning that there is a relationship between knowledge and prevention practices. Conclusions: Knowledge can influence the behavior of Indonesian people. Providing valid and well-targeted knowledge has an impact on improving behavior in community prevention efforts against Covid-19 infection.